Chemical Characteristics of Industrial Geological Parameters and Their Implications in Uranian Overview of Pa Lua - Pa Rong Area - Chau, Tran Le; Phuong, Nguyen; Giang, Nguyen Truong; Tam, Le Quyet; Phu, Nguyen Tien; Than, Nguyen Dinh; Huan, Trinh Dinh (VNU Journal of Science: Earth and Environmental Sciences; Vol 39 No 3, 2023)
This study investigated the geological properties of the uranium ore found in Pa Lua - Pa Rong area for potential industrial exploitation. A combination of field measurements, modeling and several mathematical approaches were employed to characterize the geological properties of the uranium ore. We found: i) The thickness of the ore bodies ranges from thin to medium, exhibiting varying degrees of instability (V m = 83.8÷102.8%). The average U 3 O 8 content indicates that the ore bodies belong to the poor ore type, with an unevenly distribution (V c = 57.9÷100.9%); ii) The morphology and structure of the ore bodies are highly complex, exhibiting irregular variations. The thickness of the ore bodies shows a positive correlation with the uranium content in each body (R = 0.6-0.7); iii) The variograms of the U 3 O 8 concentration and the thickness in various directions exhibit a spherical pattern, indicating an autogenous effect. The most significant variation in uranium content aligns with the dip direction (50°±12.5°), while the least variation aligns with the strike of the ore body (140°±12.5°). The variations in ore body thickness are more straightforward and consistent with those of the uranium content. In summary, these findings provide valuable insights into the characteristics of uranium ore in Pa Lua – Pa Rong area. The results contribute to a better understanding of the geological processes and can inform some effective exploration strategies for uranium resources in this region.